Demonstration of antibodies to collagen and of collagen-anticollagen immune complexes in rheumatoid arthritis synovial fluids. Issue 5 (October 1976) - Menzel, J.; Steffen, C.; Kolarz, G.; Eberl, R.; Frank, O.; Thumb, N.
Abstract : Menzel, J., Steffen, C., Kolarz, G., Eberl, R., Frank, O., and Thumb, N. (1976). Annals of the Rheumatic Diseases, 35, 446-450. Demonstration of antibodies to collagen and of collagen-anticollagen immune complexes in rheumatoid arthritis synovial fluids. Twenty-nine synovial fluids from patients with rheumatoid arthritis (RA) and 10 synovial fluids from patients with other joint diseases were investigated with regard to the presence of antibodies to denatured human collagen and of collagen-anticollagen immune complexes. 12 of the 29 RA synovial fluids showed anticollagen titres from 1: 16 to 1: 512 in passive haemagglutination. Only one patient in the group with no arthritis had a significant anticollagen titre of 1: 32. Digestion of the synovial fluids with bacterial collagenase resulted in an anticollagen titre increase from two to four dilution steps in 9 of the RA fluids, while 6 previously negative RA synovial fluids showed anticollagen titres from 1: 32 to 1: 128 after digestion with collagenase. These results indicate the existence of collagen-anticollagen immune complexes in 15 of the 29 RA synovial fluids investigated.